2019
DOI: 10.1186/s12870-019-2117-z
|View full text |Cite
|
Sign up to set email alerts
|

Identification of quantitative trait loci for increased α-tocopherol biosynthesis in wild soybean using a high-density genetic map

Abstract: BackgroundSoybean is one of the most important crop sources of tocopherols (Toc). However, the content of α-Toc, an isoform with the highest vitamin E activity in humans, is low in most cultivars. With the aim of broadening genetic variability, we performed quantitative trait locus (QTL) analysis for a high seed α-Toc trait detected in a wild soybean and characterized the sequence polymorphisms and expression profiles of γ-tocopherol methyltransferase (γ-TMT) genes as potential candidates.ResultsA recombinant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 72 publications
(83 reference statements)
0
20
0
Order By: Relevance
“…Glyma.18G115500 (located near QTN rs14143396 on Chr.18) was derived from the superfamily of NAD(P)-linked oxidoreductase. Two genes belonging to the zinc finger superfamily, including Glyma.01G021100 and Glyma.20G113200 located near QTN rs2162876 on Chr.01 and rs35562231 on Chr.20, respectively, might aid in the soybean Toc concentration with higher expressions in soybean seeds and pods ( ) ( Park et al., 2019 ). Glyma.02G102900 is a protein containing plant U-box domain (PUB26), which triggers the accumulation of Toc content by regulating the transient burst of reactive oxygen species (ROS) ( Kadota et al., 2014 ; Li et al., 2014 ; Stahl et al., 2019 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Glyma.18G115500 (located near QTN rs14143396 on Chr.18) was derived from the superfamily of NAD(P)-linked oxidoreductase. Two genes belonging to the zinc finger superfamily, including Glyma.01G021100 and Glyma.20G113200 located near QTN rs2162876 on Chr.01 and rs35562231 on Chr.20, respectively, might aid in the soybean Toc concentration with higher expressions in soybean seeds and pods ( ) ( Park et al., 2019 ). Glyma.02G102900 is a protein containing plant U-box domain (PUB26), which triggers the accumulation of Toc content by regulating the transient burst of reactive oxygen species (ROS) ( Kadota et al., 2014 ; Li et al., 2014 ; Stahl et al., 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…Toc is a member of the family of structurally-related compounds, including α -, β -, γ - and δ -Toc, and four corresponding unsaturated derivatives, α -, β -, γ - and δ -tocotrienols ( Wan et al., 2008 ). All Tocs are amphipathic molecules and contain a polar chromanol head group, which is derived from homogentisic acid and a lipophilic tail from phytyl-diphosphate ( Maheswari et al., 2015 ; Park et al., 2019 ). In soybean oil, the biological activities of four individual Tocs vary with the number and position of methyl groups on the chromanol ring ( Bramley et al., 2000 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Difference in temperature response may be resulted from genetic variations in genes involved in tocopherol biosynthesis pathway. Park et al (2019) investigated the expression level of three soybean genes (γ-TMT1, γ-TMT2, and γ-TMT3) encoding γtocopherol methyltransferase of developing seeds of TK780 (soybean, low α-tocopherol ratio) and B04009 (wild soybean, high α-tocopherol ratio) grown in 20℃ and 30℃ during seed filling. Previous studies showed that genetic variations in γ-TMT3 are associated with high α-tocopherol ratio in KAS (Dwiyanti et al 2011) and B04009 (Park et al 2019).…”
Section: Effect Of Growing Condition To Soybean Tocopherol Composition and Contentmentioning
confidence: 99%
“…Park et al (2019) investigated the expression level of three soybean genes (γ-TMT1, γ-TMT2, and γ-TMT3) encoding γtocopherol methyltransferase of developing seeds of TK780 (soybean, low α-tocopherol ratio) and B04009 (wild soybean, high α-tocopherol ratio) grown in 20℃ and 30℃ during seed filling. Previous studies showed that genetic variations in γ-TMT3 are associated with high α-tocopherol ratio in KAS (Dwiyanti et al 2011) and B04009 (Park et al 2019). Interestingly, the gene expression analysis showed that only γ-TMT2 expression level increased in both genotypes when temperature increased to 30℃.…”
Section: Effect Of Growing Condition To Soybean Tocopherol Composition and Contentmentioning
confidence: 99%